Antibacterial and antiviral potential of colloidal Titanium dioxide (TiO2) nanoparticles suitable for biological applications. (28th August 2019) - Akhtar, Sara; Shahzad, Khuram; Mushtaq, Sadaf; Ali, Iftikhar; Rafe, Muhammad Hassan; Fazal-ul-Karim, Syed Muhammad
Abstract: Present study explains the detailed synthesis, structural characterization, antibacterial and antiviral studies on Titanium dioxide nano-colloids (TiO2 -NCs). Titanium dioxide (TiO2 ) nano-colloids were synthesized by a simple sonochemical method. The structural studies were carried out by x-ray Diffraction (XRD), and the size of particle was found to be 8 nm with tetragonal structure. Surface morphological results by scanning electron microscopy (SEM), showed spherical nature of (TiO2 ) nano-colloids with almost uniform morphology. Energy Dispersive x-ray Diffraction (EDX) confirmed the chemical composition and presence of (TiO2 ) nanoparticles in sample. Dynamic light scattering was used to confirm the colloidal stability and hydrodynamic size of nano-colloids. Antibacterial assays were performed against several gram positive and negative pathogenic bacteria. TiO2 -NCs showed maximum bacterial inhibition (67.3 ± 2.5%) at 150 μ g ml − dose against Pseudomonas aeruginosa . Minimum inhibitory concentrations (MICs) against all tested pathogenic strains ranged from 2.24–21.21 μ g ml −, indicating efficient therapeutic potential of (TiO2 ) nano-colloids. Antiviral activity of (TiO2 ) nano-colloids was also performed against Newcastle virus (NDV) which showed antiviral activity at a minimum dose of 6.25 ug ml −1 . Possible mechanism of action include damage to the lipids found in viral envelop. The obtained results suggest potential application of TiO2 -NCs in poultry to treat NDV infections after detailed mechanism studies.